Performance Analysis and Testing of Aftermarket Filters - A, Srinivaas; R, Vishnu (International Journal of Engineering and Technology, 2018)
Aftermarket segment is one of the promising and growing section in automobile industry. The popularity of this section is due to the low cost and high replacement rate. Best filters among many will survive in the market. Different Filter manufacturers develop filters for same purpose but varies in their construction. There are a wide variety of aftermarket performance filters for the same type of OEMs. They vary in their brand name, filter area, filter medium, price, service life and method of install. The presence of increased number of aftermarket performance filters has prompted automotive enthusiasts to replace the OEM filter for the same purpose available in lower cost. The paper discusses about the testing procedures to be done to compare the performances both the brands (OEM and Aftermarket filters). All the experiments were conducted at PSG institute of science & Technology Coimbatore. This study shows how much an aftermarket filter varies from that of OEM. The performance of both OEMs (BOSCH and FLEETGUARD) and Aftermarket filter(UCAP) are evaluated by pressure drop, filter efficiency, media strength, porosity tests.Â Â